STABILIZATION OF TRANSISTOR ANALOGUES OF INDUCTANCE PARAMETERS - OSADCHUK, Olexander; OSADCHUK, Jaroslav; DUMENKO, Denys (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article analyzes methods for stabilizing the parameters of transistor analogues of inductance (TAI), their advantages and disadvantages are determined. Ways of implementation are considered, thanks to which it is possible to weaken the influence of all destabilizing factors, such as temperature, instability of power supplies, production variation of parameters, changes in parameters due to aging, and others. Allocated universal means to stabilize the parameters of all transistor devices. The stabilization of the operating mode at direct current and negative feedback at alternating current are considered. An assessment of the mode of instability of the parameters of the TAI was carried out by the magnitude of the increase in the equivalent inductance and quality factor. A technique for stabilizing the parameters of the TAI, as well as microwave devices, is defined, in each specific case, the need to select the allowable instability of the operating point, to perform the expected calculation of the instability of the parameters, and then to obtain the desired stability, input negative feedback on alternating current is described. The graphs of the dependence of the equivalent quality factor on temperature and the graphs of the dependence of the equivalent inductance on temperature are presented. An expression is given for the increase in inductance in the case when the main destabilizing effect on the operating mode of the transistor is a change in the reverse collector current, current transfer coefficient, collector-base voltage, emitter-base voltage, emitter current. The coefficient of regime instability was calculated. The effectiveness of stabilizing influences from negative feedback on alternating current, which contributes to the stabilization of almost all parameters of the TAI, is considered. Inductance is considered as a parameter characterizing the properties of TAI in the presence and absence of feedback. An expression is given for the relative error of inductance in the presence of NZS on alternating current.